The Tragedy of Ismena’s Fate and Character with the “Theban trilogy” of Sophocles as the Realization of Aristotle’s Catharsis Theory - Kieliszek, Zdzisław; Gocłowska, Ewa (Studia Warmińskie, 2019)
The article is dedicated to the comparative analysis of the concept of perfect tragedy presented by Aristotle in Poetics with the pathos of the fate and character of Ismene from the Three Theban Plays by Sophocles. The authors remark that the figure of Ismene sketched out by Sophocles and the course of events in which she participates correspond with the Aristotelian concept of the cathartic function of tragedy in two concurrent dimensions. The spectator is “healed” from the feeling of pity through following the sequence of consecutive events involving Ismene, as well as their directly expressed or possible consequences. By contrast, the spectator is “cleansed” of the terror through the adequate characterological features of the protagonist.